Evaluation of Different Oral Formulations of Clindamycin Extended Release in Dogs - Ortega, E.; Gutiérrez, L.; Bernad, M. J.; Salmerón, F.; Juárez, I.; Vargas, D. (Drug Research, 2017)
The purpose of this study was to evaluate the pharmacokinetics of extended-release formulations (ERFs) of clindamycin with polymeric-based matrices. In a crossover study, 21 healthy adult dogs were randomly assigned (in groups of 7) to receive a single oral dose (20 mg/kg) of clindamycin without excipients (control) or an extended-release formulation containing clindamycin+Hydroxypropyl methylcellulose (HPMC)+poloxamer at a ratio of 1 : 0.04 : 0.5 (ERF1) or containing clindamycin+HPMC+acrylic acid polymer (AAP) at the same proportions (ERF2). Serum clindamycin concentrations were determined for pharmacokinetic analysis prior to and at several time intervals after each treatment. Following the oral administration in study dogs, each ERF resulted in therapeutic serum clindamycin concentrations for 60 h, whereas the control treatment resulted in therapeutic serum clindamycin concentrations for only 12 h. All pharmacokinetic parameters for ERF1 and ERF2 were significantly different from those of the control treatment. These results indicate that both ERFs composed of a polymeric matrix containing clindamycin, HPMC, and AAP or poloxamer demonstrated an adequate pharmacokinetic-pharmacodynamic relationship for a time-dependent drug and provided a longer release period than clindamycin alone following oral administration in dogs. Given that the minimum effective serum concentration of clindamycin is 0.3 µg/mL, a dose interval of 60 h could be achieved for each tested ERF. This minimum inhibitory concentration has the potential to be effective against several susceptible bacteria involved in infections in dogs. The treatment of dogs with either ERF may provide several benefits over treatment with clindamycin alone.
Keywords: carbopol; hydroxypropyl methylcellulose; lincosamide; poloxamer